Meningkatkan Hasil Belajar Pendidikan Agama Katolik dan Budi Pekerti Menggunakan Model Pelajaran dengan Menggunakan Problem Base Learning (PBL) pada Materi Aku Citra Allah yang Unik di kelas VII SMP Negeri 3 Percut Sei Tuan. - Indra Maria Manalu (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to determine the increase in learning outcomes in Catholic Religious Education subjects for class VII students at SMP N 3 Percut Sei Tuan. This research uses a classroom research method which is carried out in two cycles. Each cycle consists of four stages, namely the planning, implementation, observation and reflection stages. The results of the research for two cycles showed a significant increase where in the first cycle the average score obtained by students when applying the PBL model was 74 and in the second cycle it was 85. This means that if the PBL learning model is applied well and consistently it will improve student learning outcomes.